Arhitekt in zasnova potresno odpornih stavb po predpisu Eurocode 8 - Slak, Tomaž (AR. Arhitektura, raziskave, 2005)
The research tackles the very wide issue of structural concepts in architecture and stems from the hypothesis that the production of earthquake resistant structures demands both a structural engineer and an architect. The research gives an expansive summary of results of several years of research and systematically deals with various topics, such as: explanations of basic terms of earthquake engineering, architect's approach, structural engineer's approach and problems linked to their cooperation, historical background of the issue etc. The research brings a collection of stipulations, regulations and rules, which an architect-designer should respect when planning the concept of an earthquake resistant building, and which emerge, this time fully, from the new Eurocode 8 standard. The issue is dealt with on the level of the idea proposal, where the architect-designer has to be as self-sufficient as possible, and the level of project for obtainment of building permit and building itself, where an architect has to cooperate with civil engineers. In this case it is necessary that the architect, as project leader, basically has knowledge about demands of technical professions and masters methods of their integration in the final project.
Keywords: potresno inženirstvo; potresna varnost; potresno varna gradnja; gradbene konstrukcije; projektiranje; standardi